(untitled) (Journal of Academic Research, 2024)
The point of view, whichh is transmitted – in its epistemological and methodological dimension – through different intellectual references, has witnessed great Interest and different reception, starting with Henry James and his followers, the Anglo-Saxon reception, passing through the structural reception of the structural narratives, such as Genit and Todorov, and ending with the verbal narratives, Krivara and Rabatal. However, the last station (verbal narratives) opened the door wide to study the point of view, In its transition from the narrow concept of neutrality, to the self, seer and utterance, and paid the recipient great attention in formulating the point of view, so the approach of Rabbatal through the theory of pronunciation and verbal linguistics, was a gateway to access the narrative text (The War of the Ghazala), to approach It according to the vision of Rabatal, whIch was translated by critic Muhammad Najib Al-Amami. This approach came to answer several questions, Including: the search for the uttered self by distinguishing between two narrative aids (the narrator and the character), ascertaining the correctness of the objectivity of the knowing narrator and the first-person narrator, the extent to which the character participates in the formation of the point of view, and highlighting the semantic function of the point of view.